Kekerasan Verbal pada Anak: Psikoedukasi pada Kader Posyandu Balita Puskesmas D Surabaya - Zafirah Hanna Qaddura (Universitas Islam Indonesia, 2021)
Verbal abuse is a type of abuse done by parents without realizing the impact caused by the abuse. The people who live around Puskesmas D Surabaya didn’t show signs of awareness about the importance of preventing verbal abuse in children. Verbal abuse continues because parents don’t understand what verbal abuse is, its impact on child’s development, and what kind of parent-child interaction to develop to avoid verbal abuse. Psychoeducation to posyandu’s kader can be an alternative that can be done to provide education to all parents around Puskesmas D Surabaya about verbal abuse. This study aims to determine the difference in knowledge of posyandu’s kader after being given psychoeducation about verbal abuse, its effects, as well as parent-child interaction that must be developed to avoid verbal abuse in children. The research method used was an experimental one group pretest-posttest design. Research respondents were 40 posyandu’s kader. The instrument used was a questionnaire compiled by researcher based on the psychoeducation materials. The result showed a difference in the pretest and posttest score with a significance of 0.000 (<0.05) which means that there is an increase in kader’s knowledge after being given psychoeducation. The result is expected to be a recommendation for Puskesmas D Surabaya to implement the psychoeducation to reduce verbal abuse in children in their working area.